Identification of the Relation between Uterine Manipulator and the Pathological Factors and Oncologic Outcome in Patients with Uterine Cancer - Ibrahimov, Akbar (Asian Pacific Journal of Cancer Nursing, 2025)
Background: Endometrial cancer (EC) is the most common gynecological cancer in developed countries, and its incidence is increasing. The uterine manipulator (UM) increases the ergonomics of surgical movement during laparoscopic total hysterectomy. Objectives: The aim of this study is to compare the surgical and oncological results of total laparoscopic hysterectomy with or without UM. Methods: One hundred seventeen EC patients who underwent total laparoscopic hysterectomy between 2018 and 2024 were retrospectively evaluated. Results: One hundred five (89.7%) of the patients were over 50 years of age, 102 (87.2%) were in the postmenopausal period, and 79 (67.5%) had a BMI >30. Tumor size was larger than 2 cm in 70 (59.8%) of the patients, and FIGO stage was I in 105 (89.7%) patients. Fifty-eight (49.6%) patients had myometrial invasion >50%, 4 (3.4%) patients had cervical involvement, 77 (65.8%) patients had lymphovascular space invasion (LVSI), 3 (2.6%) patients had adnexal involvement, and 9 (7.7%) patients had lymph node metastases. Recurrence was observed in 15 patients, and 15 patients died. Of the 95 (81.2%) patients whose procedure utilized UM, 17 had LVSI, 12 patients experienced recurrence, and 12 patients died. No significant relationship was observed between UM use and LVSI (p=0.100), recurrence (p=0.838), or survival (p=0.838). Conclusion: The use of UM in laparoscopic surgery of EC did not appear to affect LVSI, recurrence, or survival in EC.